Essentialities that Should Typify the Improvement of Health Management Processes from Science and Innovation - Yoleysi Arteaga Cuéllar; José Aurelio Díaz Quiñones; María Lina Valdés Gómez (Revista Finlay)
Health systems, as a social determinant, require continuous strengthening and optimization of their processes, so it is necessary to understand their essential qualities in order to analyze their performance and identify opportunities for improvement through science and innovation. The purpose of this work is to establish the essentialities that should typify the improvement of health management processes from science and innovation. The research focuses on the identification, systematization and critical analysis of the data obtained. For this, a qualitative methodology was used, supported by the documentary review on the topic and the experience of the authors. Initially, secondary sources of information and unstructured interviews with experts on the subject are used, with the purpose of expanding knowledge on this subject. Shortcomings were evident in the development of the management of health processes from an innovative and scientific perspective. To contribute to the improvement of health management, innovation is undeniable as a strategy that facilitates the generation of added value, productivity and organizational competitiveness in health systems and services.